Required Competencies for Business Educators’ Job Performance in Tertiary Educational Institutions in Edo and Delta States - Owenvbiugie, Osarumwense Agbonsalo; Ojeaga, Joy Ibhade (International Business Education Journal, 2022)
Business educators’ job performance has been linked to the pedagogical, problem-solving and networking competencies. Using a descriptive survey, this study investigates the extent to which business educators in Edo and Delta States, Nigeria, required such competencies for their job performance, Nigeria. 127 business educators participate in the study, and the researchers analyze the data using mean and standard deviation. The finding reveals that business educators need pedagogical, problem solving and networking competencies to high extent for job performance. Therefore, this study recommends higher education institutions to embed pedagogical, problem-solving, and networking competencies in the business education curriculum as they are very critical for job performance in today’s digitalized and competitive business environment.